Zakat Compliance: The Interplay of Religiosity, Awareness, and Knowledge - Mulyadi Firdaus; Bambang Dwi Suseno; Gema Ika Sari; Muhammad Fauzi (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study examined the influence of religiosity and knowledge of zakat on zakat awareness. It also investigates the influence of religiosity, knowledge of zakat, and zakat awareness on zakat compliance. This study involved 338 NPWZ owners who were registered as muzakki at the LPZ and lived in Serang, Banten province Indonesia. Proportional random sampling was used for respondent selection. This study used a variant-based structural equation test using PLS-SEM. The results indicate that religiosity positively influences zakat awareness and that knowledge of zakat also has a positive influence on zakat awareness. Furthermore, religiosity positively influenced zakat compliance, and knowledge of zakat enhanced zakat compliance. Higher levels of zakat awareness were correlated with increased zakat compliance. It's important to understand how much eligible Muslims actually follow through with giving zakat. This knowledge is key for gathering funds to help fight poverty and support community growth.